Complete Inactivation of Blood Borne Pathogen Trypanosoma cruzi in Stored Human Platelet Concentrates and Plasma Treated With 405 nm Violet-Blue Light - Jankowska, Katarzyna I.; Nagarkatti, Rana; Acharyya, Nirmallya; Dahiya, Neetu; Stewart, Caitlin F.; Macpherson, Ruairidh W.; Wilson, Mark P.; Anderson, John G.; MacGregor, Scott J.; Maclean, Michelle; Dey, Neil; Debrabant, Alain; et al. (Frontiers in Medicine, 2020)
The introduction of pathogen reduction technologies (PRTs) to inactivate bacteria, viruses and parasites in donated blood components stored for transfusion adds to the existing arsenal towards reducing the risk of transfusion-transmitted infectious diseases (TTIDs). We have previously demonstrated that 405nm violet-blue light effectively reduces blood-borne bacteria in stored human plasma and platelet concentrates. In this report, we investigated the microbicidal effect of 405nm light on one important bloodborne parasite Trypanosoma cruzi that causes Chagas disease in humans. Our results demonstrated that a light irradiance at 15 mWcm−2 for 5h, equivalent to 270 Jcm−2, effectively inactivated T. cruzi by over 9.0 Log10, in plasma and platelets that were evaluated by a MK2 cell infectivity assay. Giemsa stained T. cruzi infected MK2 cells showed that the light-treated parasites in plasma and platelets were deficient in infecting MK2 cells and did not differentiate further into intracellular amastigotes unlike the untreated parasites. The light-treated and untreated parasite samples were then evaluated for any residual infectivity by injecting the treated parasites into Swiss Webster mice, which did not develop infection even after the animals were immunosuppressed, further demonstrating that the light treatment was completely effective for inactivation of the parasite; the light-treated platelets had similar in vitro metabolic and biochemical indices to that of untreated platelets. Overall, these results provide a proof of concept towards developing 405nm light treatment as a pathogen reduction technology (PRT) to enhance the safety of stored human plasma and platelet concentrates from bloodborne T. cruzi, which causes Chagas disease.